Emergency department strategies to combat the opioid crisis in children and adolescents. Issue 4 (21st July 2021) - Chang, Cindy D.; Saidinejad, Mohsen; Atanelov, Zaza; Dietrich, Ann M.; Lam, Samuel Hiu‐Fung; Rose, Emily; Ruttan, Tim; Shahid, Sam; Stoner, Michael J.; Sulton, Carmen; Chumpitazi, Corrie E.; ,
Abstract: The opioid crisis has greatly affected not only adults but also children as well. As clinicians develop effective approaches to minimize pain and distress in children, the risks and benefits of opioids must be carefully considered. Children of parents with opioid use disorder are also at risk of living in unstable environments, performing poorly academically, engaging in future drug use, and having increased stress, which affects their development before entering adulthood. This statement focuses on the effects of the opioid crisis on children and adolescents and is intended to inform institutional policies, improve education, advocate for evidence‐informed guidelines, and improve the care of children affected by the opioid epidemic who are seen in the emergency department.